A Randomized Placebo Controlled Trial of Aspirin Effects on Immune Activation in Chronically Human Immunodeficiency Virus-Infected Adults on Virologically Suppressive Antiretroviral Therapy. (19th January 2017) - O'Brien, Meagan P.; Hunt, Peter W.; Kitch, Douglas W.; Klingman, Karin; Stein, James H.; Funderburg, Nicholas T.; Berger, Jeffrey S.; Tebas, Pablo; Clagett, Brian; Moisi, Daniela; Utay, Netanya S.; Aweeka, Fran; et al.
Abstract: Background: Immune activation persists despite suppressive antiretroviral therapy (ART) in human immunodeficiency virus (HIV) infection and predicts non-Acquired Immune Deficiency Syndrome (AIDS) comorbidities including cardiovascular disease. Activated platelets play a key role in atherothrombosis and inflammation, and platelets are hyperactivated in chronic HIV infection. Aspirin is a potent inhibitor of platelet activation through the cyclooxygenase-1 (COX-1) pathway. We hypothesized that platelet activation contributes to immune activation and that aspirin would reduce immune activation and improve endothelial function in ART-suppressed HIV-infected individuals. Methods: In this prospective, double-blind, randomized, placebo-controlled 3-arm trial of 121 HIV-infected participants on suppressive ART for >48 weeks, we evaluated the effects of 12 weeks of daily aspirin 100 mg, aspirin 300 mg, or placebo on soluble and cellular immune activation markers, flow-mediated dilation (FMD) of the brachial artery, and serum thromboxane B2, a direct readout of platelet COX-1 inhibition. Results: The 300-mg and 100-mg aspirin arms did not differ from placebo in effects on soluble CD14, interleukin (IL)-6, soluble CD163, D-dimer, T-cell or monocyte activation, or the other immunologic endpoints measured. Endothelial function, as measured by FMD, also was not significantly changed when comparing the 300-mg and 100-mg aspirin arms to placebo. Conclusions: Aspirin treatment for 12 weeks does not have a major impact on soluble CD14, IL-6, soluble CD163, D-dimer, T-cell or monocyte activation, or FMD, suggesting that inhibition of COX-1-mediated platelet activation does not significantly improve HIV-related immune activation and endothelial dysfunction. Although future studies are needed to further identify the causes and consequences of platelet activation in ART-treated HIV infection, interventions other than COX-1 inhibition will need to be explored to directly reduce immune activation in treated HIV infection.